Parent training of children with conduct problems: An efficacy review - Robles Pacho, Zaida; Romero Triñanes, Estrella (Anales de Psicología / Annals of Psychology, 2010)
In the last years, the scientific studies have evidenced that parent-directed interventions are decisive in the modification of early-onset problem behaviors, which frequently are markers of antisocial develop- mental trajectories. In this context, parent-training programs emerge as one of the well-researched intervention modalities, and they are considered as high-quality interventions by the scientific literature in the behavioral problems field. This study aims to review the efficacy of this kind of intervention, on the basis of results from meta-analyses and review papers collected in PSYCINFO (APA); ISOC (CSIC), ERIC and MED- LINE for the last 20 years (1989-2009). The meta-analyses and reviews which are examined in this study indicate the robustness of parent-training in the promotion of positive changes in child behaviors, in the improvement of daily parent-child interactions, and in the parental attitudes and behaviors. Moreover, parent-training programs show their efficacy in the promotion of other aspects involved in the family dynamics, such as communication, problem-solving and parental stress.